The Challenges and Aspirations of the Digital Transformation of the State Council of Egypt - Ahmad Kamal Mahmoud Ahmad, Moustafa (AUC Knowledge Fountain, 2021)
The use of modern technology to support the transformation of governmental public operations and services including judicial ones, with the aim of increasing efficiency, efficacy, and transparency, has spread all over the world, especially in the last four decades. This trend has existed in Egypt since the 1980s but without substantive efforts until the middle of the first decade of the current millennium. Since then, there have been several discussions, plans, and promises regarding the use of modern technology to enhance the effectiveness of judicial operations and services, especially in light of the increasing severe criticism directed towards the Egyptian judiciary. In recent decades, judicial operations in Egypt have suffered from severe defects resulting in, among others, a notorious delay of justice, limited enforcement of judicial orders and decisions, and a widespread lack of trust in the overall performance of the judiciary. During the last two decades, there were several attempts to introduce the use of modern technology within the Egyptian justice sector. These efforts were accompanied by frequent announcements from the Ministry of Justice and the chairs of judicial councils concerning the full automation of judicial operations and services. However, these efforts have resulted in very limited results seen in scattered and minor automation of some operations and services without the introduction of any genuine fully automated or digitally transformed operations and/or services. These poor results raise several questions about the feasibility of the automation and digital transformation of the judicial processes and services themselves. This study, which focuses primarily on the Council of State as a case study, tries to respond to these questions and other associated questions about how courts might be transformed after incorporating modern technology. It offers a view on the aspiration of the desired and long-awaited automation and digitalization; it also offers an analysis and discussion of the practical impediments that that were and still affecting the progress of the efforts of the adoption, incorporation, and implementation of modern technology and techniques of the judicial processes and services in Egypt.